Temporal changes in years of life lost associated with heat waves in the Czech Republic - Urban, Aleš; Kyselý, Jan; Plavcová, Eva; Hanzlíková, Hana; Štěpánek, Petr (The Science of the total environment, 2020)
Seniors constitute the population group generally most at risk of mortality due to heat stress. As life expectancy increases and health conditions of elderly people improve over time, vulnerability of the population to heat changes as well. We employed the years-of-life-lost (YLL) approach, considering life expectancy at the time of each death, to investigate how population ageing affects temporal changes in heat-related mortality in the Czech Republic. Using an updated gridded meteorological database, we identified heat waves during 1994-2017, and analysed temporal changes in their impacts on YLL and mortality. The mean impact of a heat-wave day on relative excess mortality and YLL had declined by approximately 2-3% per decade. That decline abated in the current decade, however, and the decreasing trend in mean excess mortality as well as YLL vanished when the short-term mortality displacement effect was considered. Moreover, the cumulative number of excess deaths and YLL during heat waves rose due to increasing frequency and intensity of heat waves during the examined period. The results show that in studies of temporal changes it is important to differentiate between mean effects of heat waves on mortality and the overall death burden associated with heat waves. Analysis of the average ratio of excess YLL/death per heat-wave day indicated that the major heat-vulnerable population group shifted towards older age (70+ years among males and 75+ years among females). Our findings highlight the importance of focusing heat-protection measures especially upon the elderly population, which is most heat-vulnerable and whose numbers are rising.
Keywords: senioři; meteorologie; Seasons; mortalita; Česká republika; vysoká teplota; naděje dožití; mužské pohlaví; Czech Republic; Heat-related mortality; ženské pohlaví; Humans; Mortality; Life Expectancy; Hot Temperature; Meteorology; Years-of-life-lost approach; Population ageing; Central Europe; Female; Aged; Heat wave; roční období; lidé; Male